IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 10 TAHUN 2011 TENTANG PAJAK PARKIR - Widodo, Monica; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2016)
Parking tax is the implementation of a parking lot otside the road, providing both concerned with a staple effort,including providing daycare motor vehicles. While park is a condition of a car who are not moving and temporary. The tax rate determined is 25% from the base tax. The basis for imposing tax is income from tax payers every month. The methodology is using qualitative approach descriptive to technique data collection the observation, interview and study documents. Informants for the research is the field of local taxes DPKAD of Semarang City. The result showed that the election parking tax of Semarang City using sell assesment and official assesment. Self assesment is a system who to vote tally number of parking tax rates totax payers an official assesment is a system to examination during 3 months. The parking tax rate determined 25% from the base tax. The parking taxdone by meanas of the total revenues tax payesr every month multiplied by 25%. But found obstacles in the system that the DPKAD of Semarang City didn’t know the reality of the total revenues from every tax payers every months. Recommendations can be done to improve the election about the mall parking taxis by tapping box machine, as they installed the box in every parking lot. That is the way if DPKAD want to know in reality the total revunue of tax payers every months.